SAT0270 TOCILIZUMAB IN REFRACTORY TAKAYASU ARTERITIS. OPEN-LABEL NATIONAL MULTICENTER STUDY OF 53 PATIENTS OF CLINICAL PRACTICE. (2nd June 2020) - Prieto-Peña, D.; Calderón-Goercke, M.; Bernabéu, P.; Vela-Casasempere, P.; Narváez, J.; Fernández-López, C.; Freire González, M.; González-Alvarez, B.; Solans-Laqué, R.; Callejas-Rubio, J. L.; Ortego, N.; Fernández-Díaz, C.; et al.
Abstract : Background: Tocilizumab (TCZ) was recently approved for Takayasu Arteritis (TAK) in Japan based on the results of the TAKT trial (1). However, data in clinical practice in Europe and America are scarce (2). Objectives: To assess efficacy and safety of TCZ in TAK of clinical practice in Spain. Methods: Observational, open-label multicentre study of 53 TAK patients treated with TCZ due to refractoriness or adverse events of previous therapy. Outcomes variables were improvement of clinical features, acute phase reactants and glucocorticoid-sparing effect. Results: 53 patients (46w/7m); mean age, 40.6±14.6 years at TCZ onset. TCZ was started after a median of 12 [3.0-48.0] months from TAK diagnosis. In addition to systemic corticosteroids and before TCZ they received conventional immunosuppressant drugs (n=42) and biologic therapy (n=14). TCZ was prescribed as standard I.V. (n=42; 79.2%) or subcutaneous (n=11; 20.8%). The initial dose was 8 mg/kg/IV/4 weeks or 162 mg/SC/week, respectively. TCZ was used in monotherapy or combined with immunosuppressants (n=32; 60.4%): methotrexate (n=27), azathioprine (n=2), cyclosporine (n=3). Main clinical features at TCZ onset were: malaise (n=30), limb claudication (n=22), headache (n=18), fever (n=14), abdominal pain (n=10), and chest pain (n=9). Most of the patients experienced a rapid and maintained clinical, analytical improvement (TABLE). After a median follow-up of 18.0 [7.0-45.0] months, TCZ was discontinued in 20 patients due to: sustained remission (n=6), relapse (n=6), adverse event (n=5), gestation (n=3). Most relevant adverse side effects were serious infections: pneumonia (n=2), herpes zoster (n=1), abdominal sepsis (n=1). Conclusion: TCZ appears to be effective and safe in patients with refractory TAK in clinical practice. References: [1]Nakaoka Y et al. Ann Rheum Dis. 2018;77:348-354 [2]Loricera J et al. Clin Exp Rheumatol. 2016; 34: S44-53. Disclosure of Interests: D. Prieto-Peña: None declared, Monica Calderón-Goercke: None declared, Pilar Bernabéu: None declared, Paloma Vela-Casasempere: None declared, J. Narváez: None declared, Carlos Fernández-López: None declared, Mercedes Freire González: None declared, Beatriz González-Alvarez: None declared, Roser Solans-Laqué: None declared, Jose Luis Callejas-Rubio: None declared, Norberto Ortego: None declared, Carlos Fernández-Díaz Speakers bureau: Brystol Meyers Squibb, Esteban Rubio Romero: None declared, SALVADOR GARCÍA MORILLO: None declared, Mauricio Minguez: None declared, Cristina Fernández-Carballido Consultant of: Yes, I have received fees for scientific advice (Abbvie, Celgene, Janssen, Lilly and Novartis), Speakers bureau: Yes, I have received fees as a speaker (Abbvie, Celgene, Janssen, Lilly, MSD, Novartis), Eugenio de Miguel Grant/research support from: Yes (Abbvie, Novartis, Pfizer), Consultant of: Yes (Abbvie, Novartis, Pfizer), Paid instructor for: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi), Speakers bureau: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi), Sheila Melchor: None declared, Eva Salgado-Pérez: None declared, Beatriz Bravo: None declared, Susana Romero-Yuste: None declared, J Salvatierra: None declared, Cristina Hidalgo: None declared, Sara Manrique Arija: None declared, C. Romero-Gómez: None declared, Patricia Moya: None declared, Noelia Alvarez-Rivas: None declared, Javier Mendizabal: None declared, Francisco Miguel Ortiz Sanjuan: None declared, I. Pérez de Pedro: None declared, Javier Loricera: None declared, Santos Castañeda: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD, Ricardo Blanco Grant/research support from: AbbVie, MSD, Roche, Consultant of: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma and MSD, Speakers bureau: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma. MSD